BIOTECHNOLOGICAL INTERVENTIONS FOR ENHANCED SECONDARY METABOLITE PRODUCTION IN MEDICINAL PLANTS - Sikarwar, Dr. Ragini (International Journal of Research -GRANTHAALAYAH, 2025)
Medicinal plants are rich repositories of secondary metabolites such as alkaloids, flavonoids, terpenoids, glycosides, and phenolics that serve as essential raw materials for pharmaceuticals, nutraceuticals, and cosmetic industries. However, their natural accumulation in planta is often insufficient, inconsistent, and subject to environmental fluctuations, making large-scale production unsustainable. Biotechnological interventions provide innovative and sustainable solutions to enhance metabolite yield, improve quality, and ensure year-round availability. This review highlights recent advancements in plant tissue culture systems (callus, suspension, and hairy root cultures), elicitor-based strategies, metabolic engineering, synthetic biology, and CRISPR/Cas9-mediated genome editing for enhancing metabolite productivity. The integration of omics platforms (genomics, transcriptomics, proteomics, and metabolomics) has enabled precise identification and regulation of key metabolic nodes. Case studies of Catharanthus roseus, Withania somnifera, and Artemisia annua are discussed to illustrate real-world applications. Although remarkable progress has been made, challenges remain, including pathway complexity, high cost of in vitro systems, and regulatory hurdles for genetically engineered plants. The article concludes that combining traditional knowledge with modern biotechnology and systems biology will accelerate the industrial-scale production of bioactive compounds, ensuring global healthcare sustainability.